L'Archéologie du frivole - Derrida, Jacques 1930-2004 (Paris Denoël/Gonthier, 1973)
In 1746 the French philosophe Condillac published his Essay on the Origin of Human Knowledge , one of many attempts during the century to determine how we organize and validate ideas as knowledge. In investigating language, especially written language, he found not only the seriousness he sought but also a great deal of frivolity whose relation to the sober business of philosophy had to be addressed somehow. If the mind truly reflects the world, and language reflects the mind, why is there so much error and nonsense? Whence the distortions? How can they be remedied? In 'L'archéologie du frivole', Jacques Derrida recoups Condillac's enterprise, showing how it anticipated--consciously or not--many of the issues that have since stymied epistemology and linguistic philosophy.
First published as introd. to E. B. Condillac's Essai sur l'origine des connaissances humaines
Includes bibliographical references.
Keywords: Condillac, Étienne Bonnot de -- 1714-1780; Philosophy; Linguistics